2018
DOI: 10.1093/cid/ciy543
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Ventilator-associated Pneumonia in Adults in Asia: An Analysis of National Income Level on Incidence and Etiology

Abstract: Ventilator associated pneumonia (VAP) is the commonest hospital acquired infection (HAI) in intensive care. In Asia, VAP is increasingly caused by resistant Gram-negative organisms. Despite the global antimicrobial resistance crisis, the epidemiology of VAP is poorly documented in Asia.We systematically reviewed literature published on Ovid MEDLINE, Embase Classic and Embase from 1st January 1990 to 17th Aug 2017 to estimate incidence, prevalence, and etiology of VAP. We performed meta-analysis of pooled data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
4
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 36 publications
2
76
4
13
Order By: Relevance
“…A continuous decrease in the VAP incidence rate and a simultaneous continuous increase in the microbiology detection rate before antibiotic use were found in hospitals in high-income provinces but not in hospitals in low-and middle-income provinces. Bonell A [35] and Hurley JC [36] also observed low VAP incidence rates in high-income areas. This may be related to the financial advantages, human resource advantages and policy advantages of highincome areas in the field of health care.…”
Section: Discussionmentioning
confidence: 91%
“…A continuous decrease in the VAP incidence rate and a simultaneous continuous increase in the microbiology detection rate before antibiotic use were found in hospitals in high-income provinces but not in hospitals in low-and middle-income provinces. Bonell A [35] and Hurley JC [36] also observed low VAP incidence rates in high-income areas. This may be related to the financial advantages, human resource advantages and policy advantages of highincome areas in the field of health care.…”
Section: Discussionmentioning
confidence: 91%
“…Although a systematic analysis of the requirement of all TCS genes in biofilm formation has not been attempted in a single study, several studies have looked at the role of many TCS components in biofilm formation. The majority of these studies were done in microtitre plates (polystyrene material), and some on PVC surface or glass surface [11,16,25,40,73,[92][93][94][95][96][97][98][99][100]. These studies have reported many TCS mutants with increased biofilm biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The ETT is the site of biofilm formation by bacteria that can dislodge into the lungs to infect the tissue [3][4][5][6][7][8][9]. Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae and Staphylococcus aureus are the most common bacterial species in the biofilm found in infected patients [10,11]. P. aeruginosa alone is responsible for 35.8 % mortality seen in VAP patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…The EU-VAP/CAP study, for example, reported an incidence density of 18.3 VAP episodes per 1000 ventilator-days [6]. Lower-middle-income countries also report higher rates compared to US hospitals and highincome countries in particular (18.5 vs 9.0 per 1000 ventilator-days; P = .035) [7]. These large discrepancies are at least in part explained by differences in definitions, differences in how definitions are applied, diagnostic limitations of all definitions, and differences in microbiological sampling methods [8].…”
Section: Epidemiologymentioning
confidence: 99%